An information systems framework to improve the issuance of identity documents through enhanced data quality in the Republic of Angola. Issue 1 (10th July 2019) - Mutudi, Maria; Iyamu, Tiko
Abstract: An individual identity document (ID) is the most important identification method within a country, for both the government and the citizens. However, the physical addresses captured and stored in the ID systems and printed on individual IDs in the Republic of Angola are consistently inconsistent, duplicated, and incorrect. As a result, government service delivery, such as basic sanitation, health care, and security are often challenged and compromised. Thus, the aim of this study was to develop an information systems framework to improve the current system that is used to issue IDs in the country. In order to achieve this aim, semistructured interviews were used to collect qualitative data. The data were collected from a governmental institution, the Ministry of Homeland, and from the community of Luanda in Angola. The data collected were hermeneutically analysed through the lens of the duality of structure from a structuration theory perspective. Based on the analysis, factors of influence were revealed and interpreted, which resulted in the development of a framework. The framework is intended to, from an information and communication technology (ICT) perspective, enhance the quality of data and improve the accuracy of issued IDs in Angola.